Soviet natural gas — A threat to Western Europe's security? - Klaus Matthies (Intereconomics, 1981)
The gas-pipeline deal planned between the Soviet Union and several Western European countries has met with objections from the US government, which fears that Western Europe could be politically blackmailed as a result of its increasing dependence on energy supplies from the USSR. Are these fears justified? Are there any realistic alternatives open to the countries concerned?
Keywords: 330; Energy